Landownership in the German Colonies of St. Petersburg Governorate from 1765 to 1914 - Shaidurov, Vladimir N.; Kayryak, Anna A. (Vestnik Rossijskogo universiteta družby narodov. Seriâ Istoriâ Rossii (Print), 2025)
The authors examine the evolution of landownership in the German colonies of St. Petersburg governorate from the second half of the 18th century to the early 20th century. The research is based on the unpublished documents found in the Russian State Historical Archive and the Central State Historical Archive of St. Petersburg. These materials include: administrative records, interdepartmental correspondence, minutes of colonists’ meetings, petitions from colonists addressed to provincial and central executive bodies, and ownership records. Most of these sources are introduced into scientific use for the first time. The research shows that in the period from 1765 to the 1810s, the St. Petersburg colonies located in close proximity to the capital were primarily established on patrimonial (later appanage) lands, which in the first half of the 19th century were under the jurisdiction of the Cabinet, the Ministry of the Imperial Court, and members of the Imperial family. Until the 1860s, these colonists utilized land allotments. However, the peasant reforms of the 1860s were extended to the German colonies as well, when they were implemented on the same general principles. The redemption payment allowed the Germans to become full owners of their land during the 1870-1890s. However, the implementation of the reforms led to drastic stratification: only homeowners (direct descendants of the first settlers in the male line) received land, while they were in the minority in the colonies. The vast majority of colonists were subsequently left landless. This gave rise to the “land question” in the colonies, which was not resolved in the pre-revolutionary period.